Celebrating the Last Supper Online: A (Swiss) Reformed Perspective - Kusmierz, Katrin (Dansk Teologisk Tidsskrift, 2022)
Can the Last Supper be celebrated online? In German-speaking Reformed Switzerland this question has not been debated widely or even controversially. There are several reasons to explain this – among others, the article suggests, the Reformed understanding of the Last Supper. So what are its liturgical and theological core characteristics? The article explores five central aspects: the Last Supper as an act of commemoration; of building and sustaining community; the importance of the Holy Spirit; the idea that the congregation should take an active role in the celebration; and the symbolic understanding of the elements of bread and wine. Can an online celebration give expression to these aspects and what are the consequences with regard to the way such a celebration is put into practice?